Peran Digital Skill dan Workforce Transformastion terhadap Kinerja UMKM - Diah Ayu Kusumawati (Jurnal Ekonomi dan Bisnis, 2022)
Business revival in the new normal era is currently the main focus for Micro, Small and Medium Enterprises (MSMEs) after nearly a year of experiencing a downturn during the pandemic. Maintaining stable performance in the new normal era is currently the main strategy for MSMEs which have a strategic role in improving the national economy. MSME actors face many problems including limited business capital, business licensing, lack of innovation, and not a few MSMEs are still stuttering about digital technology today. Therefore, the contribution of various parties is needed in an effort to improve its performance. This study aims to develop a model for improving the performance of MSMEs through digital skills, workforce transformation and digital transformation as interventions. This digital change is urgently needed for MSMEs in increasing their readiness to face the current pandemic due to the limited space for MSMEs to move. Increasing digital transformation in MSMEs needs support from digital skills and workforce transformation from MSME human resources so that it will trigger an increase in MSME performance. This research was conducted using a survey method by distributing questionnaires to 250 MSMEs in Central Java. Analysis of research data was carried out by testing structural equation modeling (SEM) and using the variance approach (partial least squares), then data processing was supported by the SmartPLS application. The results show that increasing the performance of MSMEs can be improved through digital transformation. And in improving digital transformation through digital skill readiness and carrying out HR workforce transformation, so that MSMEs are more able to compete and adapt during a pandemic.